Benzyl Phenylsemicarbazides: A Chemistry-Driven Approach Leading to G Protein-Biased Dopamine D4 Receptor Agonists with High Subtype Selectivity - Pirzer, Anna; Lasch, Roman; Friedrich, Heike; Hübner, Harald; Gmeiner, Peter; Heinrich, Markus (Journal of Medicinal Chemistry, 2019)
Many subtype-selective dopamine receptor ligands developed for the D2-D4 family incorporate a 1-arylpiperazine-derived primary recognition motif, which is connected to a lipophilic moiety occupying an extended binding pocket (EBP) of the receptor via an aliphatic linker of variable lengths. The evaluation of a novel group of dopamine receptor ligands now showed that highly subtype-selective ligands [up to Ki(D4.4) = 0.25 nM, D2L/D4.4 = 320, D3/D4.4 = 710 for APH199 (17)] can be obtained by choosing a relatively large and conformationally flexible 1-benzyl-1-phenylsemicarbazide substructure to fill the EBP. The novel chemotype APH199 (17) was found to act as a full agonist at the D4 receptor showing significant bias toward G protein activation over β-arrestin recruitment in comparison to quinpirole.
CRIS-Team Scopus Importer:2019-11-15

Radical Carbofluorination of Alkenes with Arylhydrazines and Selectfluor: Additives, Mechanistic Pathways, and Polar Effects - Pirzer, Anna; Alvarez, Eva-Maria; Friedrich, Heike; Heinrich, Markus (Chemistry - A European Journal, 2019)
Radical carbofluorination reactions starting from arylhydrazines and nonactivated alkenes, in which the C-F bond is formed through the use of Selectfluor, can be improved through the addition of anisole. Because direct trapping products could be detected only in trace amounts, anisole does primarily act as a reversible scavenger for the highly reactive ammonium radical dication released from Selectfluor in the C-F bond-forming step. As shown for three diverse substitution patterns, the main role of anisole is to prevent, or at least reduce, the undesired addition of the ammonium radical dication to the alkene, which in turn leads to an unfavorable consumption of the arylhydrazine-derived precursors required for carbofluorination. Moreover, besides the remarkable polar effects in radical trapping, this study shows that the Selectfluor-derived nitrogen-centered radical dication may add directly to alkenes, which has not been described so far.
CRIS-Team WoS Importer:2019-03-06